Alzheimer’s Disease: A Suitable Case for Treatment with Precision Medicine? - Pauwels, Ernest K.J.; Boer, Gerard J. (Medical principles and practice, 2024)
Abstract Alzheimer’s disease (AD) is the most common cause of neurodegenerative impairment in elderly people. Clinical characteristics include short-term memory loss, confusion, hallucination, agitation, and behavioral disturbance. Owing to evolving research in biomarkers, AD can be discovered at early onset, but the disease is currently considered a continuum, which suggests that pharmacotherapy is most efficacious in the preclinical phase, possibly 15–20 years before discernible onset. Present developments in AD therapy aim to respond to this understanding and go beyond the drug families that relieve clinical symptoms. Another important factor in this development is the emergence of precision medicine that aims to tailor treatment to specific patients or patient subgroups. This relatively new platform would categorize AD patients on the basis of parameters like clinical aspects, brain imaging, genetic profiling, clinical genetics, and epidemiological factors. This review enlarges on recent progress in the design and clinical use of antisense molecules, antibodies, antioxidants, small molecules, and gene editing to stop AD progress and possibly reverse the disease on the basis of relevant biomarkers. Highlights of the StudyThe heterogeneous and multifactorial nature of Alzheimer’s disease needs new therapeutic approaches.Precision medicine aims to tailor treatment to specific patients or patient subgroups.Various tailored approaches, especially genomic editing techniques, represent a promising new therapy for Alzheimer’s disease.It is highly likely that precision medicine is most efficacious at the preclinical stage of Alzheimer’s disease.